Story of Islam the heritage of Islam [videorecording] - Dooley John. ([S.l.] Polonius Production, 1991)
Summary: An overview of Islamic faith, its legacy and influence.
Keywords: Islam; Civilization, Islamic; Islamic countries -- Civilization